Thiol-redox antioxidants protect against lung vascular endothelial cytoskeletal alterations caused by pulmonary fibrosis inducer, bleomycin: comparison between classical thiol-protectant, N-acetyl-l-cysteine, and novel thiol antioxidant, N,N′-bis-2-mercaptoethyl isophthalamide - Patel, Rishi B. (2012)
Lung vascular alterations and pulmonary hypertension associated with oxidative stress have been reported to be involved in idiopathic lung fibrosis (ILF). Therefore, here, we hypothesize that the widely used lung fibrosis inducer, bleomycin, would cause cytoskeletal rearrangement through thiol-redox alterations in the cultured lung vascular endothelial cell (EC) monolayers. We exposed the monolayers of primary bovine pulmonary artery ECs to bleomycin (10 µg) and studied the cytotoxicity, cytoskeletal rearrangements, and the macromolecule (fluorescein isothiocyanate-dextran, 70,000 mol. wt.) paracellular transport in the absence and presence of two thiol-redox protectants, the classic water-soluble N-acetyl-l-cysteine (NAC) and the novel hydrophobic N,N′-bis-2-mercaptoethyl isophthalamide (NBMI). Our results revealed that bleomycin induced cytotoxicity (lactate dehydrogenase leak), morphological alterations (rounding of cells and filipodia formation), and cytoskeletal rearrangement (actin stress fiber formation and alterations of tight junction proteins, ZO-1 and occludin) in a dose-dependent fashion. Furthermore, our study demonstrated the formation of reactive oxygen species, loss of thiols (glutathione, GSH), EC barrier dysfunction (decrease of transendothelial electrical resistance), and enhanced paracellular transport (leak) of macromolecules. The observed bleomycin-induced EC alterations were attenuated by both NAC and NBMI, revealing that the novel hydrophobic thiol-protectant, NBMI, was more effective at µM concentrations as compared to the water-soluble NAC that was effective at mM concentrations in offering protection against the bleomycin-induced EC alterations. Overall, the results of the current study suggested the central role of thiol-redox in vascular EC dysfunction associated with ILF.